Multifocal Osteosarcoma: Unusual Presentation and Imaging Findings. (April 2017) - Gavane, Somali; Price, Anita P.; Magnan, Heather; Mahajan, Sonia; Pandit-Taskar, Neeta
Abstract : Abstract: Multifocal osteosarcoma is usually defined as the occurrence of a tumor at 2 or more sites in a patient without pulmonary metastases and may be synchronous with more than one lesion seen at presentation or metachronous with new tumors developing after the initial treatment. It is difficult to determine whether these represent synchronous multiple primary lesions or metastases. We present a rare case of widespread synchronous multifocal osteosarcoma and a brief review of the literature.